Building Brand Relationship: An Examine The Relationship Among Restaurant Attributes, Other Customers, Brand Image, Customer Satisfaction, Brand Trust, And Brand Preference - Daud Alfredo Hidayat Mulyana; Ronald , Ronald; Amelia, Amelia (SEAN Institute, 2024)
The results obtained by store atmosphere and other customer does not affect the brand image, Food quality, Service quality significantly affect brand image, Store atmosphere, Food quality, Service quality, other customer significant effect customer satisfaction, other customer and Brand image does not affect customer satisfaction, Brand image significant effect brand trust, Customer satisfaction significant effect brand trust and brand trust significant effect brand preference.